\(\dfrac{-1}{6}+\dfrac{2}{3}.\left(-\dfrac{3}{4}\right)+\dfrac{\left(-2\right)^2}{5}\\ =\dfrac{-1}{6}-\dfrac{1}{2}+\dfrac{4}{5}\\ =\dfrac{-5}{30}-\dfrac{15}{30}+\dfrac{24}{30}\\ =\dfrac{4}{30}\\ =\dfrac{2}{15}\)
\(-\dfrac{1}{6}+\dfrac{2}{3}.\left(-\dfrac{3}{4}\right)+\dfrac{\left(-2\right)^2}{5}\\ =-\dfrac{1}{6}+-\dfrac{1}{2}+\dfrac{4}{5}\\ =\dfrac{-5}{30}-\dfrac{15}{30}+\dfrac{24}{30}\\ =\dfrac{2}{15}\)
\(=-\dfrac{1}{6}-\dfrac{1}{2}+\dfrac{4}{5}=-\dfrac{5}{30}-\dfrac{15}{30}+\dfrac{24}{30}=\dfrac{4}{30}=\dfrac{2}{15}\)